A Review on the Construction, Modeling, and Consistency of Digital Twins for Advanced Air Mobility Applications - Tianxiong Zhang; Dominik Grzelak; Wanqi Zhao; Md Ashraful Islam; Hartmut Fricke; Uwe Aßmann (Drones)
The advent of Advanced Air Mobility (AAM) presents a transformative solution to multi-modal transportation. However, coordinating missions, as well as monitoring and controlling multiple Unmanned Aerial Vehicles (multi-UAV systems), remains a significant challenge. The adoption of digital twin (DT) technology has the potential to provide a viable solution. This study synthesizes insights from 145 publications across the UAV, traditional aviation, and manufacturing domains, retrieved from major scientific databases such as Scopus, IEEE Xplore, and ScienceDirect. The aim is to comprehensively analyze advancements in cyber–physical systems (CPS) and DT technologies, with a particular focus on the key aspects of UAV-based DT construction, including framework architecture, geometric modeling, physical modeling, behavioral modeling, rule modeling, and cyber–physical consistent modeling approaches. Additionally, the application of DTs in AAM scenarios is analyzed, and key challenges are identified. Finally, we provide insights into research directions to enhance the robustness and applicability of future AAM-based DT.